Mortgages and Pledges in Contemporary Islamic Commercial Law: A Study of Their Application - Dr. Tahira Ifraq (Al Manhal Research Journal, 2024)
In the realm of economics and finance, which deals with monetary matters, Islamic principles guide financial activities in accordance with Sharῑʻah law. While profit generation is permissible in Islam, it must align with ethical guidelines. Unlike conventional systems that often rely on ribā (interest) and exploitative practices, Islamic finance promotes compassion, community, and the fulfillment of needs. Ribā is viewed as an unjust mechanism that concentrates wealth and denies fundamental rights to the masses, with Islamic economics aiming for equitable wealth distribution. Security in financial transactions is crucial, as it fosters trust and ensures the performance of obligations. In Islamic commercial law, the concept of rahn encompasses various forms of collateral, including pledges and mortgages, to safeguard against default. This system allows lenders to extend interest-free loans with confidence, as it supports societal welfare. Rahn operates under specific rules and principles that protect both creditors and debtors, preventing any party from taking undue advantage. Islamic financial institutions offer Sharia-compliant products, including rahn, which serves both as a security mechanism for transactions like Murābahah and as an independent offering. This article explores the mortgages and pledges provided by Islamic financial institutions, with an emphasis on the regulations set forth by the Accounting and Auditing Organization for Islamic Financial Institutions concerning pledges. It explores the application of rahn across various products and its role as a standalone offering, particularly in Islamic pawn broking. Additionally, the article delves into the Islamic mortgages and home financing schemes available through these institutions, highlighting their unique features and compliance with Sharῑʻah principles.